Analysis of an Implicit Fully Discrete Local Discontinuous Galerkin Method for the Time-Fractional Kdv Equation (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we consider a fully discrete local discontinuous Galerkin (LDG)finite element method for a time-fractional Korteweg-de Vries (KdV) equation. Themethod is based on a finite difference scheme in time and local discontinuous Galerkinmethods in space. We show that our scheme is unconditionally stable and convergentthrough analysis. Numerical examples are shown to illustrate the efficiency and accuracyof our scheme.